Hubungan Tahajud dengan Perilaku Merokok pada Mahasiswa Fakultas Kedokteran Universitas Islam Indonesia - Jiva Yori Anugrah; Nur Aisyah Jamil; Pariawan Lutfi Ghazali (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2010)
Marker of stress in human could be seen by increased level of cortisol in the blood. The higher level of stress, the higher cortisol level in the blood. Smoking would accelerate the release of endorphin in the central nervous system which causes a sense of happy and then stress trigger will be reduced. According to Sholeh in 2001, tahajud could reduce the level of cortisol in the human body. This study was done to understand the relationship between tahajud and smoking among students in Medical Faculty of Islamic Indonesian University (FK U/1). This was a non experimental cross sectional study. The sample in this study were students of FK U/1 in academic semester year 2010/2011. Sampling was conducted by cluster random sampling technique and sample size were 100 students. The p value was obtainedsignificant(p<0,01) that tahajud has a relationship with smoking behavior between femalo respondens, while in male repondens were not. The conclusion showed that there is a relationship between tahajud and smoking in female student.